Histopathologic Features of Antibody Mediated Rejection: The Banff Classification and Beyond - Cornell, Lynn D. (Frontiers in Immunology, 2021)
Antibody mediated rejection (ABMR) in the kidney can show wide range of clinical presentations and histopathologic patterns. The Banff 2019 classification currently recognizes four diagnostic categories: 1. Active ABMR, 2. Chronic active ABMR, 3. Chronic (inactive) ABMR, and 4. Accommodation (C4d staining without evidence of rejection). This categorization is limited in that it does not adequately represent the spectrum of antibody associated injury in allograft, it is based on biopsy findings without incorporating clinical features (e.g., time post-transplant, de novo versus preformed DSA, protocol versus indication biopsy, complement inhibitor drugs), the scoring is not adequately reproducible, and the terminology is confusing. These limitations are particularly relevant in patients undergoing desensitization or positive crossmatch kidney transplantation. In this article, I discuss Banff criteria for these ABMR categories and offer a framework for considering the continuum of allograft injury associated with donor specific antibody.